Heterogeneity and the nonparametric analysis of consumer choice: Conditions for invertibility - Walter Beckert; Richard Blundell (Centre for Microdata Methods and Practice (cemmap), 2005)
This paper considers structural nonparametric random utility models for continuous choice variables. It provides suffcient conditions on random preferences to yield reduced- form systems of nonparametric stochastic demand functions that allow global invertibility between demands and random utility components. Invertibility is essential for global identification of structural consumer demand models, for the existence of well-specified probability models of choice and for the nonparametric analysis of revealed stochastic preference.
Keywords: C14; C31; C51; D1; 330; nonparametric random utility model; stochastic demand; global invertibility